How Perceived Corporate Social Responsibility Raises Employees’ Creative Behaviors Based on Appraisal Theory of Emotion: The Serial Mediation Model - Id Bouichou, Said; Wang, Lei; Zulfiqar, Salman (Frontiers in Psychology, 2022)
The present study examined the micro-level consequences of perceived corporate social responsibility (CSR) and hypothesized that perceived CSR affects the perception-emotion-attitude-behavior sequence. We hypothesized that perceived CSR affects organizational pride (emotion), which affects affective commitment (attitude), which enhances the employees’ creative behaviors (behavior) by using the lens of appraisal theory of emotion. This study also hypothesized that the association of perceived CSR and employee creative behaviors is serially mediated by organizational pride and affective commitment. Time-lagged data was collected from employees of only those companies who are actually participating in CSR activities to analyze the sequential mediation effect. We have tested the hypotheses of the present study through Hayes (2013) approach. Results showed that perceived CSR kindles the employees’ creative behaviors. Furthermore, “organizational pride” and “affective commitment” serially mediate the perceived CSR-employee creative behavior association. Hence, the hypothesized perception-emotion-attitude-behavior model got significant support and demonstrated that micro-level positive consequences of CSR could be created through emotion, attitude, and behavior mechanisms.